2022
DOI: 10.3389/fpubh.2022.880435
|View full text |Cite
|
Sign up to set email alerts
|

The Negative Impact of COVID-19 in HCV, HIV, and HPV Surveillance Programs During the Different Pandemic Waves

Abstract: BackgroundThe coronavirus disease 2019 (COVID-19) pandemic has been a worldwide stress test for health systems. 2 years have elapsed since the description of the first cases of pneumonia of unknown origin. This study quantifies the impact of COVID-19 in the screening program of chronic viral infections such as human papillomavirus (HPV), human immunodeficiency virus (HIV), and hepatitis C virus (HCV) along the six different pandemic waves in our population. Each wave had particular epidemiological, biological,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 19 publications
2
6
0
Order By: Relevance
“…Due to shifting healthcare restrictions, lockdowns and travel bans worldwide, a large number of migrant populations might not have been able to reach our ED. The impact of the pandemic reducing the number of HIV diagnoses has also been reported by other groups in multiple countries [48–53]. Regarding late diagnosis and missed opportunities, data from 12 September 2018 to 11 September 2019 are unaffected by the COVID‐19 pandemic and still show a reduction in late diagnosis, mean number of previous healthcare encounters and percentage of patients with at least one healthcare encounter, all of which hints favourably at the benefit of our intervention.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Due to shifting healthcare restrictions, lockdowns and travel bans worldwide, a large number of migrant populations might not have been able to reach our ED. The impact of the pandemic reducing the number of HIV diagnoses has also been reported by other groups in multiple countries [48–53]. Regarding late diagnosis and missed opportunities, data from 12 September 2018 to 11 September 2019 are unaffected by the COVID‐19 pandemic and still show a reduction in late diagnosis, mean number of previous healthcare encounters and percentage of patients with at least one healthcare encounter, all of which hints favourably at the benefit of our intervention.…”
Section: Discussionsupporting
confidence: 70%
“…Regarding late diagnosis and missed opportunities, data from 12 September 2018 to 11 September 2019 are unaffected by the COVID‐19 pandemic and still show a reduction in late diagnosis, mean number of previous healthcare encounters and percentage of patients with at least one healthcare encounter, all of which hints favourably at the benefit of our intervention. Given the impact of the COVID‐19 pandemic on worldwide detection of HIV in general, we can speculate about an increase in the late diagnosis rate in the coming years, but this has not been reported so far [ 48 , 49 , 50 , 51 , 52 , 53 ]. Despite these limitations, our study demonstrated a robust methodology to generate essential HIV diagnoses and epidemiology data.…”
Section: Discussionmentioning
confidence: 99%
“…Our study reveals the actual increased risk of C. trachomatis generating new variants ( 30 ), which could be endowed with distinct tropisms, exploiting new ecological niches and spreading to other population groups. Efforts should, therefore, be undertaken to strengthen screening and surveillance programs, especially in the current situation with the continuous increase in STI infections and the post-pandemic SARS-CoV-2 period in which numerous screening programs were interrupted ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although this healthcare system is the largest in Taiwan, the data may not represent the entire country or other regions. In addition, throughout the coronavirus disease 2019 (COVID-19) pandemic, COVID-19 has had a negative impact on the diagnosis of new HPV cases [ 41 ]. The study’s timeframe partially overlapped with the COVID-19 pandemic (December 2020).…”
Section: Discussionmentioning
confidence: 99%